2023
DOI: 10.3389/fpubh.2023.1118207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smart device use on objective and subjective health of older adults: findings from four provinces in China

Abstract: BackgroundThe digital divide has grown because of the deepening digitalization of the Chinese society and the intersection between high-end technology and the age structure. Older adults show an increasing level of weakness in digital life integration. What digital development can bring to older adults is a pressing concern.ObjectiveThis study aims to investigate how smart device use affects older adults' health status and offers an empirical reference for improving their digital literacy and health.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Furthermore, the subjects are smartphone users who have registered accounts with ASMILE; thus, the study assumes that they are naturally highly conscious about health. A study reported that smartphone use is associated with a greater perceived health status, especially among older adults living in urban areas [62]. It is speculated that a moderate use of smartphones will improve the mental and physical health of older people by encouraging them to connect with the outside world and communicate with others and by making it easier to obtain useful health information.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the subjects are smartphone users who have registered accounts with ASMILE; thus, the study assumes that they are naturally highly conscious about health. A study reported that smartphone use is associated with a greater perceived health status, especially among older adults living in urban areas [62]. It is speculated that a moderate use of smartphones will improve the mental and physical health of older people by encouraging them to connect with the outside world and communicate with others and by making it easier to obtain useful health information.…”
Section: Discussionmentioning
confidence: 99%